(untitled) (Ágora Journal, 2022)
This paper aims to analyze the perception of the Portuguese Cortes (1821-1822) in the works by Manuel de Oliveira Lima (1867-1928). He demonstrates a view of History based on a political liberalism that is identified with the so-called Whig History. In the following sections, this manuscript examines the relations between Whig History and liberal ideas and how Oliveira Lima dealt with liberalism, particularly on his books on the Brazilian Empire. In the last section, the text focuses on the discussion on the Portuguese Cortes, emphasizing the debates on whether the Portuguese Constitution should recolonize Brazil, breaking the regimes of liberty that arose from the presence of the Royal Family in Rio de Janeiro.